The power of saying no : the new science of how to say no that puts you in charge of your life - Patrick, Vanessa M. (Sourcebooks, 2023)
"Everyone has a hard time saying no, but doing so can vastly improve our lives and relationships. Enter the art of empowered refusal: the skill of strategically saying no from a place of personal power that gives voice to your principles, values, and priorities while protecting your relationships and reputations. In Power of Saying No, Professor and researcher Vanessa Patrick explains that empowered refusal is a much-needed framework that can be mastered with thoughtful practice. By setting boundaries and being respectful to others (and yourself!) saying no can help you live your happiest, most successful life"--